PENGARUH KOMPENSASI EKSEKUTIF, CAPITAL INTENSITY DAN FINANCIAL DISTRESS TERHADAP TAX AVOIDANCE - Putri, Marcelia Anindya; Abidin, Jaenal (Publika Citra Media, 2025)
This study aims to analyze the influence of Executive Compensation, Capital Intensity and Financial Distress on Tax Avoidance. This study was conducted by analyzing financial reports and annual reports of companies operating in the mining sector listed on the Indonesia Stock Exchange (BEI) for a 6 year period (2018-2023). The sample used in this study was 12 companies taken based on purposive sampling technique. The data used in this study is secondary data in the form of financial reports and annual reports from each company used as the study sample. The independent variables in this study are Executive Compensation, Capital Intensity and Financial Distress, while the dependent variable is Tax Avoidance. This study uses the panel data regression method. Analysis of study results using the Eviews 12 Student Lite Version tool. The study results show that the best model to use in this study is the Cammon Effect Model (CEM). The study results show that Executive Compensation has no effect on Tax Avoidance, Capital Intensity has an effect on Tax Avoidance, and Financial Distress also has no effect on Tax Avoidance.